COMPARISON OF SEISMIC EFFECTS FROM NUCLEAR AND CHEMICAL EXPLOSIONS - Kopnichev Yu.F.; Spivak A.A. (My University, 1997)
Experimental data were used to derive relations between seismic magnitude m and the weight of charge q for underground nuclear explosions for peaceful purposes and for industrial chemical blasts. A steeper relation m(q) was obtained for chemical explosions owing to complex seismic source geometries: in contrast to an almost spherically symmetrical nuclear source, an ordinary shallow chemical explosion commonly has a significantly extended charge distribution.